The Self Lost, the Self Adjusted: Forming a New Identity in Bereavement Memoirs by American Women - Małecka, Katarzyna (Studia Anglica Posnaniensia, 2016)
Most Western cultures place a great value on autonomy. American society in particular has always stressed the need to succeed via self-reliance, a characteristic which, in recent decades, has additionally manifested itself in an increasing inclination for self-examination reflected in the deluge of autobiographical writing, especially memoirs. This analysis focuses on memoirs of spousal loss, a specific subgenre of life writing in which, due to the loss of a loved one, the narrating self realizes how unstable a sense of autonomy is. In their bereavement narratives, Joan Didion, Anne Roiphe, and Joyce Carol Oates admit that after losing a life partner their world crumbled and so did their sense of self. The article examines the following aspects of the grieving self: 1. how grief tests one’s self-sufficiency; 2. how various grief reactions contribute to self-disintegration; 3. the widow as a new and undesirable identity; and 4. writing as a way of regaining one’s sense of self.